2008
DOI: 10.1038/ajh.2008.35
|View full text |Cite
|
Sign up to set email alerts
|

Nephrectomy Modifies Renal Angiotensin II Effects in Kidney Donors

Abstract: In normotensive donors with a normal compensatory response to nephrectomy, baseline renal reactivity to angiotensin II can influence renal and glomerular hemodynamics 1 year after nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…For kidney donors, donation does not seem to negatively impact long-term outcome in appropriately selected subjects (4). Renal function is partially balanced by the remaining kidney through compensatory changes after unilateral nephrectomy, namely, mild enlargement of the kidney, an approximate 60% increase in glomerular filtration rate (GFR), near 20% increase in the filtration fraction, and 40% increase in effective renal plasma flow (5). The mean GFR has been found to be in the order of 70% to 75% of the prenephrectomy values (6).…”
mentioning
confidence: 99%
“…For kidney donors, donation does not seem to negatively impact long-term outcome in appropriately selected subjects (4). Renal function is partially balanced by the remaining kidney through compensatory changes after unilateral nephrectomy, namely, mild enlargement of the kidney, an approximate 60% increase in glomerular filtration rate (GFR), near 20% increase in the filtration fraction, and 40% increase in effective renal plasma flow (5). The mean GFR has been found to be in the order of 70% to 75% of the prenephrectomy values (6).…”
mentioning
confidence: 99%
“…In addition, human studies report higher rates of HDP in women with preexisting kidney disease (4). After donor nephrectomy, the GFR of the remaining kidney increases by 40%, and its response to hormones such as angiotensin II is altered (7). On (9,10) and maternal death is less than 0.1% (11).…”
Section: The Complex Codependent Relationships Between Kidney Functimentioning
confidence: 99%
“…4 One kidney ERPF decrease after Ang II was enhanced by nephrectomy in absolute, but not relative terms, whereas glomerular filtration rate, not modified by Ang II before nephrectomy, decreased both in absolute and relative values after nephrectomy, with a consequent filtration fraction decrease. Table 1 shows the data of our 26 donors before and after nephrectomy.…”
mentioning
confidence: 99%
“…3 In an earlier study on kidney donors we found that nephrectomy shifts the action of Ang II from the afferent towards the efferent arteriole, 4 increasing efferent resistance and filtration pressure. Although this study revealed a shift in the site of action of Ang II, it did not analyze possible changes in sensitivity to this hormone after loss of renal tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation